SIFAT FISIK DAN KIMIA SUP KRIM INSTAN DENGAN PENAMBAHAN HIDROLISAT PROTEIN DAGING KAMBING KACANG - Irdha Mirdhayati; Wieda Nurwidada (State Islamic University of Sultan Syarif Kasim Riau, 2019)
Meat protein hydrolyzate can be used as an ingredient in making instant cream soup. The application of mutton protein hydrolyzate as an ingredient in making cream soup has never been done. The purpose of this study was to develop instant cream soup products from goat meat hydrolyzate as a functional food product prototype, and to know the characterization of instant cream soup in terms of its physical and chemical properties. This research is an experiment with a completely randomized design, with replications 3 times. The treatment is the addition of goat meat protein hydrolyzate which consists of 6 levels, namely, 0%, 0.2%, 0.4%, 0.6%, 0.8% 1.0% and commercial cream soup as a comparison. Data on physical properties and chemical composition were analyzed statistically by diversity analysis. The results showed that the addition of goat meat protein hydrolyzate at different concentrations was able to increase bulk density and pH value and reduce the water binding capacity of instant cream soup produced. The addition of goat meat protein hydrolyzate at different concentrations increases the water content and protein content, decreases the carbohydrate content of instant cream soup, but does not affect the ash content and fat content. It can be concluded that the addition of goat meat hydrolyzate to 1% produces instant cream soup with the same pH value and water binding capacity as commercial cream soup products and produces higher protein content than commercial products.